Istifādah min āl-Kalimāti Zātu Aslin ‘Arabi fî KBBI li Ta’līmi Mahārah Al-Istimā’ ladā Al-Indūnīsiyyīn - Nadya Salsabila; Arif Taufikurrohman (Mauriduna: Journal of Islamic Studies, 2021)
منذ مجيء الإسلام واللغة العربية في إندونيسيا تأثرت اللغة الإندونيسية تأثر كبيرا باللغة العربية وتصير اللغة الإندونيسية تقترض من اللغة العربية. ولذلك هذه اللغة ساهمت في إثراء خزنة مفردات اللغة الإندونيسية، ومع ذلك لا ينتبه كثير من الشعب الإندونيسي بوجود الكلمات الإندونيسية التي لها أصل عربي في لغتهم الأم. وهذا تهدف هذه الدراسة إلى التعرف على وجود الكلمات الإندونيسية لها أصل عربي في مهارة الاستماع للإندونيسيين. إن هذه الدراسة تسلك على منهج المكتبي والوصفي دون تحليل الكلمات لها أصل عربي، وذلك تتبع الكلمات الإندونيسية في قاموس اللغة الإندونيسية الكبير التي تحليلها الباحث أحمد سبيل الرشاد في حرف J. وبلغ عدد الكلمات الإندونيسية لها أصل عربي 68 كلمة. وأثبتت أيضا على أنها تنقسم على أربعة أقسام، وهي ما لا تغير فيه لفظا ومعنى، وماكان فيه تغير لفظا ومعنى ومعنى لا لفظا، ولفظا لا معنى. ونمكن الاستفادة من تلك الكلمات خاصة في تعليم مهارة الاستماع ووضعها في التدريبات والحوارات والنصوص والألعاب اللغوية. Since the arrival of islam in indonesia, though rapidly developing developing trade, indonesia’s development began, especially in terms of language which greatly influenced indonesian vocabulary into absorption words from Arabic. Therefore, this language plays a role in the enrichment of indonesian vocabulary, but many indonesians do not pay attention to indonesian words that have Arabic that are derived from their narative languge. Thus, this study aims to identify the benefits of teaching indonesian vocabulary absorption from Arabic in indonesian listening skills. This research proves the existence of indonesian dictionaries analyzed by researcher Ahmad Sabila Rasadi on the letter J. The number of indonesian vocabulary uptake from Arabic reaches 68 words. And it is evident that the vocabulary is divided into four parts, namely vocabulary that does not change in meaning and not verbally, and verbally meaningsless. And can utilize vocabulary especially in teaching listening skills and placing them in practice, dialogue, text and language games.